Within‐guild dietary discrimination from 3‐D textural analysis of tooth microwear in insectivorous mammals. (27th August 2013) - Purnell, M. A.; Crumpton, N.; Gill, P. G.; Jones, G.; Rayfield, E. J.
Abstract Resource exploitation and competition for food are important selective pressures in animal evolution. A number of recent investigations have focused on linkages between diversification, trophic morphology and diet in bats, partly because their roosting habits mean that for many bat species diet can be quantified relatively easily through faecal analysis. Dietary analysis in mammals is otherwise invasive, complicated, time consuming and expensive. Here we present evidence from insectivorous bats that analysis of three‐dimensional (3‐D) textures of tooth microwear using International Organization for Standardization (ISO) roughness parameters derived from sub‐micron surface data provides an additional, powerful tool for investigation of trophic resource exploitation in mammals. Our approach, like scale‐sensitive fractal analysis, offers considerable advantages over two‐dimensional (2‐D) methods of microwear analysis, including improvements in robustness, repeatability and comparability of studies. Our results constitute the first analysis of microwear textures in carnivorous mammals based on ISO roughness parameters. They demonstrate that the method is capable of dietary discrimination, even between cryptic species with subtly different diets within trophic guilds, and even when sample sizes are small. We find significant differences in microwear textures between insectivore species whose diet contains different proportions of 'hard' prey (such as beetles) and 'soft' prey (such as moths), and multivariate analyses are able to distinguish between species with different diets based solely on their tooth microwear textures. Our results show that, compared with previous 2‐D analyses of microwear in bats, ISO roughness parameters provide a much more sophisticated characterization of the nature of microwear surfaces and can yield more robust and subtle dietary discrimination. ISO‐based textural analysis of tooth microwear thus has a useful role to play, complementing existing approaches, in trophic analysis of mammals, both extant and extinct.